2018
DOI: 10.1111/sjpe.12165
|View full text |Cite
|
Sign up to set email alerts
|

Location choices and third‐degree spatial price discrimination

Abstract: This paper studies how firms choose their product differentiation levels when they engage in third‐degree price discrimination in the following product market competition in a location‐price model. We show that firms will not choose to locate at the two endpoints if different consumer groups have similar sizes. Hence, the principle of maximum differentiation does not hold, resulting in a more intense product market price competition. Only if the size of one group of consumers is sufficiently larger than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…They show that if the quality levels of the local firms' products are the same, price discrimination always increases welfare, mainly because of a positive allocation effect of price discrimination [17]. Feng and Ma investigated (2018) how firms choose their level of product differentiation when engaging in third-degree price discrimination in a competitive product market; their results show that firms will only set themselves at the two end points to make their products as differentiated as possible if one group of consumers is sufficiently larger than the other [18]. Zhang, T. et al, (2019) considered location monopoly and found that price discrimination improves social welfare when demand elasticity is large enough [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They show that if the quality levels of the local firms' products are the same, price discrimination always increases welfare, mainly because of a positive allocation effect of price discrimination [17]. Feng and Ma investigated (2018) how firms choose their level of product differentiation when engaging in third-degree price discrimination in a competitive product market; their results show that firms will only set themselves at the two end points to make their products as differentiated as possible if one group of consumers is sufficiently larger than the other [18]. Zhang, T. et al, (2019) considered location monopoly and found that price discrimination improves social welfare when demand elasticity is large enough [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, in our model, firms can choose their location and thereby influence the segmentation. In addition, in contrast to our model in Liu and Serfes (2004) and Feng and Ma (2018) consumers in all segments are aware of all firms.…”
Section: Related Literaturementioning
confidence: 69%
“…In particular, we analyze whether consumers benefit from higher levels of perception. Although firms in our analysis discriminate with respect to the perception of consumers, because of our setup this corresponds to charging different segments on the Hotelling line different prices (e.g., Fudenberg and Tirole, 2000;Liu and Serfes, 2004;Choe, King, and Matsushima, 2018;Feng and Ma, 2018). 11 In Fudenberg and Tirole (2000) and Choe, King, and Matsushima (2018), a firm offers different prices to its own past consumers and its rival's past consumers.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation